The type of antiresorptive treatment influences the time to onset and the surgical outcome of medication-related osteonecrosis of the jaw - Pautke, Christoph; Wick, Alexander; Otto, Sven; Hohlweg-Majert, Bettina; Hoffmann, Jürgen; Ristow, Oliver (Journal of oral and maxillofacial surgery, 2021)
Purpose - Few data exist focusing on differences in the time to disease onset and the success rates in patients suffering from medication-related osteonecrosis of the jaw (MRONJ) dependent on their different antiresorptive treatment. The purpose of this study was to analyze and compare these variables for patients treated with bisphosphonate (BP) or denosumab (DNO) and for patients who switched the antiresorptive drug (BP/DNO). - Patients and Methodss - A retrospective single-center cohort study with patients suffering from MRONJ was conducted. The predictor variable was the antiresorptive treatment, the outcome variables were 1) time to onset of MRONJ (time of antiresorptive treatment to MRONJ diagnosis) and 2) treatment success (mucosal integrity 12 months postoperatively). The other variables include data on demographic, underlying disease, MRONJ stage, and trigger events. Cox and logistic regression, Phi-coefficient, Cramer's V, and Kruskal-Wallis tests were applied. - Results - One hundred thirty-two patients were included and divided into 3 groups: group I (BP) n = 45 patients, n = 59 lesions; group II (BP/DNO) n = 42 patients, n = 71 lesions; and group III (DNO) n = 45 patients, n = 62 MRONJ lesions. Treatment success and time to onset differed significantly between the groups: success rates in group I BP (84.7%) were significantly lower (P = .04) than in group II BP/DNO (91.5%, P = .12) and group III DNO (90.3%, P = .35). The onset was significantly earlier in group III DNO (median 2.0 years, Q0.25: 1.49, Q0.75: 2.98; confidence interval 95%: 1.93 to 2.83) than in group II BP/DNO (median 4.07 years, Q0.25: 1.64, Q0.75: 6.70; confidence interval 95%: 3.55 to 5.68) and group I BP (median 3.86 years, Q0.25: 1.69, Q0.75: 6.46; confidence interval 95%: 3.43 to 5.87). - Conclusions - The different antiresorptive drugs show distinctive characteristics of time to onset and treatment success with the lowest success rates in the BP group and the earliest onset in the DNO group. The switch of the antiresorptive therapy (BP to DNO) did not influence the outcome variables negatively.
Gesehen am 19.05.2021
First published: 13 October 2020